1981
DOI: 10.2172/6403917
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal plasma rotation in the PLT tokamak with neutral-beam injection

Abstract: Toroidal plasma rotation in the Princeton Large Torus, PLT, has been measured for various plasma and neutral beam injection conditions. Measurements of the plasma rotational velocities were made from Doppler shifts of appropriate spectral lines and include data from both hydrogen and deuterium beams and co-and counter-injection at several electron densities. Without injection, a small but consistent toroidal rotation exists in a direction opposite to the plasma current (counter-direction) in the plasma center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…While this assertion is true in the usual neoclassical ordering of Hsu and Sigmar, it is not in their 'strong impurity' ordering, where A =~ 0 (1) for a = n I Z 2 /n i ~ 0(1). Thus, the arguments which Connor et al [28] present to support their contention that the solution of Stacey et al [13b] for Kj is 'unphysical' and that the numerical result (no ordering approximations) that \d%/dd\ -|eO 0 | is 'flawed' are themselves invalid in the strong impurity limit of Hsu and Sigmar.…”
Section: Gyroviscous Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…While this assertion is true in the usual neoclassical ordering of Hsu and Sigmar, it is not in their 'strong impurity' ordering, where A =~ 0 (1) for a = n I Z 2 /n i ~ 0(1). Thus, the arguments which Connor et al [28] present to support their contention that the solution of Stacey et al [13b] for Kj is 'unphysical' and that the numerical result (no ordering approximations) that \d%/dd\ -|eO 0 | is 'flawed' are themselves invalid in the strong impurity limit of Hsu and Sigmar.…”
Section: Gyroviscous Theorymentioning
confidence: 95%
“…We use a right hand (^, p, <f>) flux surface co-ordinate system (e.g. [9]) with differential length elements, d£ x = h x dx, and a differential volume element, = 2TT dip B P (1) where B p is the 'poloidaT magnetic field. The flux surface average of a quantity A is (A) = 2TT Ad j (2) in this co-ordinate system, and the volume integral of a quantity A is (A) V'…”
Section: Flux Surface Co-ordinate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a deuterium plasma has reached toroidal velocities of approximately 40 % the sound speed in the DIII-D tokamak (Baylor et al 2004, figure 9) and the National Spherical Torus Experiment (NSTX) has reported toroidal velocities of approximately half the Alfvén speed (Sabbagh et al 2006, p. 641). Rotation is typically induced by neutral beam injection (known as NBI) or radio-frequency (known as RF) heating (Suckewer et al 1981;Eriksson, Righi & Zastrow 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Rotation is typically induced by neutral beam injection (known as NBI) or radio-frequency (known as RF) heating (Suckewer et al. 1981; Eriksson, Righi & Zastrow 1997).…”
Section: Introductionmentioning
confidence: 99%